PELATIHAN LATEX MENGGUNAKAN OVERLEAF DALAM UPAYA KOLABORASI ITT PURWOKERTO DENGAN UNIBA SERANG - Miftahul Huda; Ridho Ananda; Rani Septiani Sukandar (Jurnal Abdimas Bina Bangsa, 2023)
The LaTex training using Overleaf aims to provide participants with the skills and knowledge to use LaTex and the online platform, Overleaf, to create scientific and academic documents. The training covers basic LaTex topics, including document structure, formatting, and typesetting, as well as more advanced topics, such as creating mathematical formulas and technical illustrations. In addition, participants will learn how to use Overleaf to enable collaborative work, document synchronization, and document sharing in various formats. In this training, participants will be given hands-on learning experiences through exercises, activities, and direct practice on the use of LaTex and Overleaf. Instructors will also provide feedback and active interaction with participants in each training session. By completing this training, participants will have the ability to create high-quality scientific and academic documents using LaTex and Overleaf and be able to apply it to their own research and writing projects. This training is highly recommended for anyone who wants to improve their skills in creating high-quality scientific and academic documents and to increase their work efficiency.